(untitled) (Semiárida, 2020)
In this contribution, three genera and eight species of Lemnaceae growing in the province of La Pampa, Argentine, are keyed, described and illustrated. One genus: Wolffia Horkel and five species: Lemna parodiana Giardelli, Lemna dispersa lIegelmaier, Lemna minima Philippi, Wolffia papulifera Thompson y Wolffia columbiana Karsten are mentioned for the first time to this region.